Metal-assisted chemical etching for designable monocrystalline silicon nanostructure. (April 2016) - Li, Meicheng; Li, Yingfeng; Liu, Wenjian; Yue, Luo; Li, Ruike; Luo, Younan; Trevor, Mwenya; Jiang, Bing; Bai, Fan; Fu, Pengfei; Zhao, Yan; Shen, Chao; et al.
Graphical abstract: Highlights: The review summarizes the recent contributions in silicon nanostructure by MACE. The fundamental principle, basic manipulation process, and new developed technologies and potential applications are presented. Abstract: Metal-assisted chemical etching (MACE) is a simple, low-cost and versatile method of fabricating various silicon nanostructures. Due to the etching anisotropy of monocrystalline silicon, i.e. its different crystal orientation has different number of silicon back bonds needed to be broken in the etching process, the obtained silicon nanostructures are morphology variable. It has been demonstrated that, by choosing the species or morphologies of catalyst, adjusting the etchant composition or concentration, changing the doping species and level of the silicon substrate, or introducing extra physical fields, MACE method can be used to prepare various desired silicon nanostructures. This review summarizes the most recent contributions in the fabrication of designable monocrystalline silicon nanostructure by MACE. In order to provide a relatively complete comprehension of the MACE, the fundamental principle and basic manipulation process of a conventional MACE, as well as the main influence factors on the etching effects are given; and the common applications of MACE in silicon etching are briefly reviewed. This article also presents some new developed improved MACE technologies and their potential applications in the extended field.